Aceptabilidad y efectos adversos de la ablación térmica en el primer nivel de atención para prevenir el cáncer cervical, Loreto, 2021-2024 - Wong Cossio, Cristina Elizabeth (2025)
Objective: To determine the level of acceptability and evaluate the adverse effects of thermal ablation (TA) in women attended at the primary care level for cervical cancer prevention in the Loreto region during the period 2021 2024. Methods: Observational, cross-sectional, and retrospective study conducted in three local health centers with a sample of 210 women selected through non-probabilistic sampling. Data collection was carried out through structured questionnaires applied via telephone. Acceptability was evaluated using a Likert scale, and pain experienced during the procedure was measured using the Wong–Baker FACES® scale. Adverse effects were recorded using the DAIDS classification. Results: Acceptability was high (average Likert scale score of 3.95 out of 5), with participants rating the experience as better than expected; 95.2% indicated willingness to repeat the procedure, and 98.1% would recommend it to other women. Pain reported during the procedure was minimal or absent in 80.5% of cases. Immediate adverse effects were mostly mild, including slight bleeding (17.6%), mild nausea (1.4%), and mild headache (1.9%). At 4-6 weeks, mild watery vaginal discharge (37.6%) and mild bloody secretion (22.9%) predominated. Only 6.2% required additional medical care. Conclusions: Thermal ablation demonstrated high acceptability with predominantly mild adverse effects, suggesting its viability as a safe intervention for cervical cancer prevention at the primary care level.